Peran Pendidikan Agama Islam dalam Meningkatkan Kepedulian terhadap Pelestarian Lingkungan di Timbang Langkat Binjai Timur - Muhammad Rangga Pramana; Muhammad Hidayat (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines how Islamic Religious Education (PAI) contributes to developing student character that reflects care for environmental sustainability. The growing phenomenon of environmental degradation requires education that goes beyond cognitive aspects and nurtures ecological awareness grounded in Islamic values. The aim of this research is to describe the strategies and implementation of PAI in fostering environmentally friendly behavior among students. This study employs a qualitative approach through interviews with PAI teachers, observations of student activities, and documentation related to school-based environmental programs. The findings reveal that Islamic teachings on cleanliness, environmental balance, and human responsibility as stewards of the earth provide a strong foundation for encouraging students to protect the environment through positive habits such as proper waste disposal, wise use of resources, and participation in greening activities. Nevertheless, the implementation still faces several challenges, including inconsistent student discipline and limited supporting facilities within the school. Overall, PAI serves as an educational medium capable of shaping ecological behavior when supported by strong collaboration between schools, teachers, and families.